(untitled) (Trabalho & Educação, 2016)
Agricultural extension is an educational process involving farmers and extension workers that aims at rural development. This study investigated how agricultural extension contributes to the improvement of lives and production conditions of small-scale farmers in Brazil. For ten months, I observed the work of five extension workers (or “extensionists”) at a public agency for a project that involved 260 families, totaling more than one-thousand individuals. My hypothesis was that improvement would be reduced because the extension workers had limited knowledge of the complexity of small-scale farming. This hypothesis was supported by my findings. The results of the fieldwork pointed out that rural extension has been an important means of creating resources that result from public policies available to rural communities. These resources were essential to improving the lives of the farmers by offering, for example, social benefits to the individuals and providing them with better housing conditions. On the other hand... ___ A extensão rural tem como objetivo promover o desenvolvimento no campo por meio de um processo educativo junto aos agricultores. Este estudo investigou como o trabalho dos extensionistas contribui para a melhoria da qualidade de vida e das condições de produção dos agricultores familiares. Durante dez meses, observou-se o trabalho de cinco extensionistas participantes de um projeto envolvendo 260 famílias de agricultores quilombolas em um município da região norte de Minas Gerais. A hipótese geral que orientou esta pesquisa foi de que o apoio dos extensionistas aos agricultores teria seu efeito reduzido pelo conhecimento limitado dos técnicos acerca da complexidade da produção familiar. Os resultados do trabalho de campo evidenciaram que a extensão rural tem sido um veículo importante para que recursos disponibilizados pelas políticas públicas das diferentes esferas de governo alcancem as comunidades rurais. Esses recursos mostraram-se fundamentais para a melhoria da qualidade de vida dos agricultores familiares: na oferta de benefícios sociais, no provimento de melhores condições de habitação, no acesso à água e à energia elétrica. Por outro lado...